Cognitive processing of persuasive messages: the concept of peripheral routes of persuasion through visual cues of celebrity endorsements in advertisements - Adzharuddin, Nor Azura (2014)
The purpose of this paper is to examine the cognitive processing of persuasive messages through the concept of peripheral routes of persuasion from Elaboration Likelihood Model (ELM) using celebrity endorsements as visual cues in advertisements. The focus of the analysis is on advertisements containing images of celebrities, integrated through different channels of marketing communication. Inconsistent persuasive messages including different images of celebrity endorsements exposed to consumers can result into confusion; thus, create less favourable effects in consumers' minds. Findings have shown that advertisements exposed in different media were significantly related to consumers' memory foe advertisements. Consumer can have higher memory recall of advertisements when advertisements with similar visual cues were repeated in different media. However, visual cues must be consistently repeated in different media to get the maximum outcome. Without elaboration or little argument quality and in a low involvement setting, consumers would choose to process the information they saw through the peripheral routes. This would direct the attention of consumers to only the peripheral cues in the advertisement. In this case, the peripheral cues used were the image of a celebrity. If advertisers could apply the ELM concept in the new media advertising setting whilst integrating it with similar concept in the traditional media, better memory recall can be encouraged. The current advertising trend has shown increasing efforts to emphasize on the integration of different media which includes new media using consistent visual cues. Nevertheless, studies on peripheral routes of persuasion of ELM focusing on celebrity's image are still lacking within the Malaysian multicultural context, especially using the experimental approach.